Transcription elongation. Issue 3 (27th May 2017) - Mustaev, Arkady; Roberts, Jeffrey; Gottesman, Max
ABSTRACT: This review is focused on recent progress in understanding how Escherichia coli RNAP polymerase translocates along the DNA template and the factors that affect this movement. We discuss the fundamental aspects of RNAP translocation, template signals that influence forward or backward movement, and host or phage factors that modulate translocation.